ANTIBACTERIAL ACTIVITY OF FENNEL LEAVES ETHANOL EXTRACT (FOENICULUM VULGARE MILL) AGAINST PSEUDOMONAS AERUGINOSA - Ahwan Abdul; Fadilah Qonitah; Partonowati _ (Universitas Muhammadiyah Magelang, 2021)
Fennel leaf (Foeniculum vulgare Mill) is an herbal plant that is used for treatment. Flavonoid compounds and essential oils contained in fennel leaves have an antibacterial effect. The purpose of this study was to determine the activity of fennel leaf extract against Pseudomonas aeruginosa bacteria. Testing of antibacterial activity using a pure experimental method with a randomized design with a unidirectional pattern using the extraction method, namely maceration and bacterial activity testing with the diffusion method. The parameter measured is the diameter of the inhibition formed in the paper disc area. The data were measured using the Anova statistical approach. Fennel leaf extract has an inhibitory effect on the growth of Pseudomonas aeruginosa bacteria, namely at concentrations of 15% (11.04 ± 1.59 mm), 25% (13.68 ± 3.54 mm), 50% (18.14 ± 2.04 mm), 75% (20.53 ± 0.88 mm) and 100% (22.82 ± 0.32 mm) compared with 1% Dimethyl Sulfoxide (DMSO) negative control (00.00 ± 0.00 mm), while the test with positive control Gentamicin 1% (22.82 ± 0.32 mm) with a strong category (10 - 20 mm), namely at concentrations of 15%, 25% and 50%, very strong category (>20mm), namely at concentrations of 75% and 100%, the statistical significance value of ANOVA was p<0.05. It can be concluded that the ethanol extract of fennel leaf (Foenicullum vulgare Mill) has antibacterial activity against Pseudomonas aeruginosa. The value of the minimum inhibitory concentration (MIC) of ethanol extract of fennel leaf (Foenicullum vulgare Mill) against Pseudomonas aeruginosa bacteria was 15% w/v.